2007
DOI: 10.1103/physrevb.76.035417
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between stability, electronic, and structural properties of cagelike and spherical nanodiamond clusters

Abstract: Ab initio density functional theory calculations were used to investigate cohesive, electronic, and structural properties of cagelike and spherical hydrogen terminated nanoparticles of diamond. Unlike cagelike nanodiamond particles, the variation of calculated energies of spherical ones is not monotonic. The variation range of the calculated energies and bond lengths of cagelike nanoparticles is much tighter than the variation range of spherical ones. In contrast to spherical nanodiamond particles, the C-C bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…From Ref. 12 we know that for the cagelike C particles, the formation energy increases and HOMO-LUMO energy gap decreases monotonically in agreement with monotonic variation in CH/ CH 2 +CH 3 ratio with the size. For the spherical C particles, the variation in formation energy and HOMO-LUMO energy gap with size reach a maximum and a minimum, respectively, 12 in agreement with nonmonotonic variation in CH/ CH 2 +CH 3 ratio with the size.…”
Section: Correlation Between Electronic Structure and Surface Chõ supporting
confidence: 64%
See 2 more Smart Citations
“…From Ref. 12 we know that for the cagelike C particles, the formation energy increases and HOMO-LUMO energy gap decreases monotonically in agreement with monotonic variation in CH/ CH 2 +CH 3 ratio with the size. For the spherical C particles, the variation in formation energy and HOMO-LUMO energy gap with size reach a maximum and a minimum, respectively, 12 in agreement with nonmonotonic variation in CH/ CH 2 +CH 3 ratio with the size.…”
Section: Correlation Between Electronic Structure and Surface Chõ supporting
confidence: 64%
“…6, we have shown the variation in the CH/ CH 2 +CH 3 ratio with the nanoparticle size for cagelike and spherical nanodiamond particles and also in the inset of this figure we have shown the variation in the HOMO-LUMO energy gap of the cagelike and spherical particles with the size. 12 In Fig. 6, for the cagelike nanodiamond particles there is a monotonic increase in the ratio of CH/ CH 2 +CH 3 with size whereas the variation in this ratio for spherical particles is not monotonic and has a maximum value for C 35 H 36 .…”
Section: Correlation Between Electronic Structure and Surface Chõ mentioning
confidence: 92%
See 1 more Smart Citation
“…In order to investigate the relative stability of bare and hydrogenated nanodiamond in this work, formation energy for each carbon atoms has been calculated according to the following equation [11,31]:…”
Section: Resultsmentioning
confidence: 99%
“…Raty et al [10] theoretically investigated the stability of bare and hydrogenated diamond with generalize gradient approximation (GGA) and they found that for particles between 2 and 3 nm, the hydrogenated diamond are less favored energetically in comparison to the bare diamond. Saani et al [11] used B3LYP exchange-correlation functional to investigate the stability and electronic properties of spherical and cage-like structure of hydrogenated nanodiamond. They showed that the spherical shapes of nanodiamond are more stable than the cage-like structures.…”
Section: (151)mentioning
confidence: 99%